Kansvatter: Die rustelose lewe van Ben Viljoen - Coetzee, Emile (Scientia Militaria - South African Journal of Military Studies, 2021)
To write a biography is a daunting task but if done correctly and fairly, it can be a magnificent piece of historical literature. A biography, and especially an autobiography, is a literary genre that can assist any historian to see past events directly through the eyes of the person about whose life is being written. Some historical figures can boast a long list of biographies due to their popularity during their lifetime or shortly after it. Others are either merely mentioned briefly in other publications or their biographies are limited due to a variety of external factors. When it comes to Benjamin Johannis (or is it Barend Johannes?) Viljoen, his life story is finally explained thoroughly for the first time by the Stellenbosch historian, Dr Carel van der Merwe.